2014
DOI: 10.1108/jmtm-06-2012-0065
|View full text |Cite
|
Sign up to set email alerts
|

Environmental sustainability in logistics and freight transportation

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 93 publications
4
96
0
3
Order By: Relevance
“…In fact, environmental issues were hardly mentioned in previous 3PL literature reviews [15][16][17]. A number of literature reviews on this topic have been published [18][19][20][21][22]. Nevertheless, several limitations plague these reviews.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, environmental issues were hardly mentioned in previous 3PL literature reviews [15][16][17]. A number of literature reviews on this topic have been published [18][19][20][21][22]. Nevertheless, several limitations plague these reviews.…”
Section: Introductionmentioning
confidence: 99%
“…The two database were selected because they provide a broad coverage of management journals. This searching procedure is widely accepted and has been adopted in previous literature reviews [18,21,22,32,33]. The third step includes the definition of both searching and the inclusion/exclusion criteria.…”
Section: Planning the Review Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Ilgin and Gupta [1] indicated that CLSCM is simultaneously controlled by upstream and downstream channels; whereas Guide and Van Wassenhove [48] stated that reverse material flows dominate the forward supply chains within CLSCM operations. Reverse logistics, which is also described as reverse SCM, is part of the process that collects used materials within CLSCM aimed at maintaining environmental sustainability within SCM [6,56,57]. Kongar et al [57] emphasized that reverse logistics activities focus on finding environmentally, economically, and socially sustainable solutions through the transparency of information with regards to the logistics flows.…”
Section: Closed-loop Supply Chain Managementmentioning
confidence: 99%
“…The purpose of the formal analytical integrated model is the determination of the logistics center energy Z(E Log ) = energy status of intra-logistics base elements (energy demand); Z(E GTA ) = energy status of building technology base elements (energy demand); w i = impacts and interrelation between base elements due to specific parameters; v i = behavioral impacts of the base elements due to their technical parameters; u i = impacts from the environment due to boundary parameters; w 1 = losses (technological loads) as process-oriented heat source; w 2/3 = energy recovery/process-independent heat source; w 4 = characteristics of building material; w 5 = material flow layout; w 6 = regulatory requirements for energy efficiency and fire protection; v 1 = operational task (payload, acceleration, distance, . .…”
Section: Mathematical Modelingmentioning
confidence: 99%